Motivos para a prática esportiva e o senso de autoeficácia em atletas - Kyrillos, Michel Habib Monteiro (2016)
Currently, the practice of sport is a social phenomenon that includes a number of psychological factors that can be decisive in the sporting conduct. Thus, the study of motivational factors and self-efficacy beliefs is essential for the development and maintenance of athletes in sports programs. Thus, the objectives of this work are: a) identify and analyze the reasons for sports and self-efficacy in Sergipe athletes; b) Compare the reasons for sports and self-efficacy in athletes who receive no financial aid or the Athlete Grant program (study 1); c) To analyze the reasons for sports to individual sports athletes (Study 2); d) To analyze the factors that influence self-efficacy of individual sports athletes (Study 3). It was identified that in all the extrinsic reasons athletes are prevalent as well as a high self-efficacy, with variation from the presence of financial aid. When analyzed only athletes from individual sports, the results indicate that the main reasons for participation are considered extrinsic, such as competition, physical fitness and technical expertise. There are several factors that influence self-efficacy in individual sports athletes, not be a predominant factor. It follows that the reasons presented as the most important were Competition, Technical and Physical Fitness competence, considered as extrinsic and self-efficacy suffers variation in athlete's function having or not financial aid. In individual sports, the most valued motivational factors were the competition, the Technical Competence and Physical Fitness, which are considered as extrinsic reasons. The more experience and higher competitive level, there is a decrease in the average score of why athletes performing a sport. Perhaps the selfefficacy varies depending on the sport that is practiced, where athletes swimming had a sense of self-efficacy higher than the others. Sex, age, practice time and the competitive level alone are not decisive to influence self-efficacy.